Anecdotes of University Students in Learning Chemistry: A Philippine Context - Mangubat, F. M. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Contrasting approaches, principles, and previous learning experiences widely confront chemistry instruction. Therefore a comprehensive and precise understanding of the nature and mechanism of chemistry instruction is essential in attaining mastery of science subjects like chemistry. This study explored the determinants that affect students’ chemistry in tertiary education. This study utilized an explanatory sequential mixed-method research design wherein quantitative data is collected and analyzed. Qualitative data was collected and analyzed based on quantitative results. The respondents (n=253) were the students who took their chemistry subjects from 2016-2017, 2017-2018, 2018-2019, and 2019-2020. The study revealed that the type of school significantly affects students’ chemistry learning. Based on students’ responses, it was revealed that classroom dynamics, a supportive learning environment, the prospect for attractive compensation, poor study habits, non-aligned of academic track, and teachers are the determinants affecting students’ academic performance in chemistry.